Effects of rural electrification on employment - Bensch, Gunther,Gotz, Gunnar,Peters, Jörg (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
This paper replicates and extends the seminal paper by Dinkelman (2011) on the impacts of electrification on female employment. We revisit the validity of the identification strategy that uses the land gradient as an instrumental variable (IV). Our robustness checks cast doubt on the exclusion restriction as the IV drives the outcome variable in non-electrified regions. We also demonstrate that it is more difficult to disentangle the effects of electricity and road infrastructure than the original paper claims, because the IV affects both. We additionally highlight that the IV is weak, consequently preventing interpretation of the point estimates that are used throughout the original paper. The concomitance of a questionable exclusion restriction and a weak IV is particularly problematic. We conclude by arguing that the takeaways of the original paper for policy and the academic literature need to be reconsidered. In general terms, our comment shows the difficulties of using geographical variation as a natural experiment for infrastructure evaluation.
10.4419/86788973
Keywords: Graue Literatur; Replication; research transparency; energy access; infrastructure; instrumental variables